(untitled) (Journal of Dhaka Medical College, 2023)
Introduction: Diabetes Mellitus (DM) is a worldwide health problem. Patients with type 2 diabetes mellitus are at increased risk of infections, with urinary tract being the most common site. UTI may be asymptomatic in DM patient. Worldwide there is a high frequency of antibiotic resistance. This study is designed to determine the causative organism of UTI in diabetic patient as well as their resistance pattern. Methods: This cross sectional descriptive study was conducted in semiurban multispeciality hospital of Feni for a period of nine month from January 2020 to September 2020. One hundred consecutive culture positive UTI in diabetic patient were enrolled in this study. UTI with negative urine culture were excluded from the study. The organism isolated in culture and antibiotic sensitivity was noted. Results: Age of this study population ranges from 20 to 80 years. Out of 100 patients with 39%were male and 61% were female. Twenty percent of the UTI were asymptomatic. E. coli was the commonest causative organism found in 64% cases, followed by Klebsiella 11% & Proteus 7%. Overall 84% organism were resistant to amoxicillin & 72% were resistant to quinolones. Most organism were sensitive to meropenem with only 11% resistance. Sixty percent of the isolates were resistant to 3 or more antibiotics. Conclusion: E. coli being the commonest causative organism with very high frequency of antibiotic resistance & multidrug resistance. J Dhaka Med Coll. 2022; 31(1) : 5-8